The Role of Interdisciplinary Collaboration between Nurses and Nutritionists in Enhancing Patient Outcomes - Samia Salama Ali Al Enezy; Noura Jbran Namazi; Falak Ahmed Ali Jaffal; Asma Mansour Alrashidi; Waed Fahed Alenazi; Zainab Ali Hussain Bosroor; Ahmed Hamed Mohammed Alnowmasi; Zaid Mosaad Zaid Alharbi; Sami Abdulhalim Abdullah Albudaiya; Ahmed Mohammed Ibrahim Assiri; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Interdisciplinary collaboration between healthcare professionals has long been recognized as a cornerstone of effective patient care. Among the most vital partnerships in healthcare are those between nurses and nutritionists (or dietitians), who together provide comprehensive care aimed at improving patient outcomes, particularly in complex health conditions such as tuberculosis (TB), chronic diseases, and malnutrition. This paper explores the synergistic benefits of collaboration between nurses and nutritionists, focusing on how their combined expertise enhances patient care through comprehensive nutritional management, improved adherence to treatment regimens, and holistic patient education. A review of relevant literature, case studies, and practical examples demonstrates the positive impact of this collaboration on patient outcomes, including faster recovery, reduced complications, and higher patient satisfaction.